Comparative Evaluation of Four Bacteria-Specific Primer Pairs for 16S rRNA Gene Surveys - Thijs, Sofie; Op De Beeck, Michiel; Beckers, Bram; Truyens, Sascha; Stevens, Vincent; Van Hamme, Jonathan D.; Weyens, Nele; Vangronsveld, Jaco (Frontiers in Microbiology, 2017)
Bacterial taxonomic community analyses using PCR-amplification of the 16S rRNA gene and high-throughput sequencing has become a cornerstone in microbiology research. To reliably detect the members, or operational taxonomic units (OTUs), that make up bacterial communities, taxonomic surveys rely on the use of the most informative PCR primers to amplify the broad range of phylotypes present in up-to-date reference databases. However, primers specific for the domain Bacteria were often developed some time ago against database versions that are now out of date. Here we evaluated the performance of four bacterial primers on complex microbial communities of an explosives contaminated and non-contaminated forest soil and by in silico evaluation against the current SILVA123 database. Primer pair 341f/785r produced the highest number of bacterial OTUs, phylogenetic richness, Shannon diversity, low non-specificity and most reproducible results, followed by 967f/1391r and 799f/1193r. Primer pair 68f/518r showed overall low coverage and a bias towards Alphaproteobacteria. The primer pair 341f/785r showed also in silico the highest coverage of the domain Bacteria (96.1 %) with no obvious bias towards the majority of bacterial species. This suggests the high utility of primer pair 341f/785r for soil and plant-associated bacterial microbiome studies.